2015
DOI: 10.5301/jva.5000506
|View full text |Cite
|
Sign up to set email alerts
|

Which Arm and Vein are more Appropriate for Single-Step, Non-Fluoroscopic, Peripherally Inserted Central Catheter Insertion?

Abstract: Right-arm access through the basilic or brachial vein may be more appropriate for successful nonfluoroscopic PICC insertion compared with the access through the left arm and the cephalic vein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
0
5
0
4
Order By: Relevance
“…Currently, there is a lack of definite evidence related to arm selection. Several studies have favoured the right side 19 20. However, a study by Minkovich et al showed that a left-sided approach might be more suitable because it produced a lower incidence of malposition 21.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is a lack of definite evidence related to arm selection. Several studies have favoured the right side 19 20. However, a study by Minkovich et al showed that a left-sided approach might be more suitable because it produced a lower incidence of malposition 21.…”
Section: Discussionmentioning
confidence: 99%
“…Além deste, há um estudo que mostra a preponderância da seleção ao membro superior direito (13) . Uma pesquisa mostrou que o membro superior direito tem maior taxa de sucesso de inserção na primeira tentativa do que o membro superior esquerdo (14) . Contudo, alguns estudos mostram a seleção do braço (15)(16) não dominante e sendo esse a maioria o membro superior esquerdo (14) .…”
Section: Discussionunclassified
“…), что коррелирует с литературными данны-ми [1,4,5]. Установленный факт свидетельствует о необходимости применения интраоперационной рентгеноскопии, однако результаты, полученные некоторыми авторами, позволяют рассматривать установку ЦКПВ под мониторингом интраопераци-онной электрокардиограммы (ЭКГ) [6][7][8]. На наш взгляд, ЭКГ-контроль с применением современных навигационных систем, например Bard Sherlock (Bard Access Systems, Inc., США), может служить альтернативой установке с использованием ана-томических ориентиров.…”
Section: оригинальные статьиunclassified